The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1038/s41420-018-0100-3
|View full text |Cite|
|
Sign up to set email alerts
|

PIDD-dependent activation of caspase-2-mediated mitochondrial injury in E1A-induced cellular sensitivity to macrophage nitric oxide-induced apoptosis

Abstract: Expression of the adenovirus E1A oncogene sensitizes tumor cells to innate immune rejection by apoptosis induced by macrophage-produced tumor necrosis factor (TNF)-α and nitric oxide (NO). E1A sensitizes cells to TNF-α and NO through two distinct mechanisms, by repressing NF-κB-dependent antiapoptotic responses and enhancing caspase-2 activation and mitochondrial injury, respectively. The mechanisms through which E1A enhances caspase-2 activation in response to NO were unknown. Here, we report that E1A-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
3
6
0
Order By: Relevance
“…The data presented here define PIDD–caspase-2 as the key, post-recognition cellular pathway through which E1A enhances target cell susceptibility to NK-cell-mediated cytolytic activity, as a complementary mechanism to E1A-induced increased expression of NKG2D ligands 6 . These results and our previously reported data also suggest that PIDD-dependent caspase-2 activation enhancement is a common cellular mechanism through which E1A sensitizes cells to a variety of stimuli of the intrinsic apoptosis pathway, including macrophage-NO and proapoptotic chemotherapeutic drugs 11,12,16 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The data presented here define PIDD–caspase-2 as the key, post-recognition cellular pathway through which E1A enhances target cell susceptibility to NK-cell-mediated cytolytic activity, as a complementary mechanism to E1A-induced increased expression of NKG2D ligands 6 . These results and our previously reported data also suggest that PIDD-dependent caspase-2 activation enhancement is a common cellular mechanism through which E1A sensitizes cells to a variety of stimuli of the intrinsic apoptosis pathway, including macrophage-NO and proapoptotic chemotherapeutic drugs 11,12,16 .…”
Section: Discussionsupporting
confidence: 87%
“…5c, d). These data and those published previously strongly suggest that E1A expression enhances caspase-2 activation through the PIDDosome in response to a variety of intrinsic apoptotic injuries 11,16 , including those mediated by NK cells.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…34,35 E1A makes cells sensitive to nitric oxide by inducing mitochondrial dysfunction−mediated apoptosis. 36 We observed that mitochondrial morphology was different in 3Y1 and E1A-3Y1 cells. Therefore, it is possible that expression of E1A could modify mitochondrial functions or structures, making cells more sensitive to mitochondrial stresses such as prethioviridamide treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 71%